PHILOSOPHICAL ANALYSIS OF CONSUMPTIVE ECONOMIC BEHAVIOR IN RELIGION - Abdul Wahid (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2021)
The economic system arises because of human efforts to meet the needs of life, so that economic activities are formed, such as production, distribution, and consumption. Consumption is an important (even very important) activity in human life. In other words, the role of humans in the dynamics of their lives, must intersect and require consumption in the form of social interactions. However, all human activities, especially consumer behavior cannot be separated from the ways and rules that have been set in religion. In principle, religion (in this case Islam) should have to answer the many formulations of problems related to consumptive economic behavior. Religion implies that consumer behavior is not limited to the necessities of life that are real or visible in reality, but must also be based on an abstract or transcendental point of view. Thus, human behavior in the economy is not only fixated on the aspects of pleasures that emphasize the material aspects but also the spiritual aspects.